Anti-CD20 therapies in multiple sclerosis: From pathology to the clinic - de Sèze, Jérôme; Maillart, Elisabeth; Gueguen, Antoine; Laplaud, David A.; Michel, Laure; Thouvenot, Eric; Zephir, Hélène; Zimmer, Luc; Biotti, Damien; Liblau, Roland (Frontiers in Immunology, 2023)
The immune system plays a significant role in multiple sclerosis. While MS was historically thought to be T cell-mediated, multiple pieces of evidence now support the view that B cells are essential players in multiple sclerosis pathogenic processes. High-efficacy disease-modifying therapies that target the immune system have emerged over the past two decades. Anti-CD20 monoclonal antibodies selectively deplete CD20+ B and CD20+ T cells and efficiently suppress inflammatory disease activity. These monotherapies prevent relapses, reduce new or active magnetic resonance imaging brain lesions, and lessen disability progression in patients with relapsing multiple sclerosis. Rituximab, ocrelizumab, and ofatumumab are currently used in clinical practice, while phase III clinical trials for ublituximab have been recently completed. In this review, we compare the four anti-CD20 antibodies in terms of their mechanisms of action, routes of administration, immunological targets, and pharmacokinetic properties. A deeper understanding of the individual properties of these molecules in relation to their efficacy and safety profiles is critical for their use in clinical practice.